Studies on the text of Caesar's Bellum civile - Damon, Cynthia (Oxford University Press, 2015)
'Studies on the Text of Caesar's Bellum Civile' is a companion volume to Damon's revised 'Oxford Classical Texts' edition of Caesar's 'Bellum civile', his account of his civil war with Pompey. Comprising three parts, it investigates the detailed philological arguments that underpin the revised edition of the text